Generation Y’s Behavioural Usage of Small Businesses’ Retail Websites in Canada - Lim, Allen Chong Guan (Curtin University, 2019)
This research delves into the factors that influence Generation Y’s usage of Canadian small businesses’ retail websites in order to suggest how they can be attracted to use them more. Based on the Use of Technology Two (UTAUT2) theory, questionnaire survey and semi-structured interviews revealed linkages between Behavioural Intention, Habit, Facilitating Conditions and Use Behaviour with demographic variables moderating some relationships. Improving the website designs and social media marketing can entice Generation Y consumers.